(untitled) (Analysis in Theory and Applications, 2023)
Under some natural regularity assumptions on the exponent function, we obtain the boundedness of Marcinkiewicz integrals μ, μ^ρ_S and μ^∗,ρ_λ on grand variable Herz spaces. Our results enrich and improve some previous results in the literature.